A complexation study of 2,6-bis(1-(p-tolyl)-1H-1,2,3-triazol-4-yl)pyridine using single-crystal X-ray diffraction and TRLFS - Kiefer, Claude; Wagner, Anna. T.; Beele, Björn B.; Geist, Andreas; Panak, Petra; Roesky, Peter W. (Inorganic chemistry, 2015)
To develop a selective ligand for the separation of lanthanides(III) and actinides(III) the coordination chemistry of the chelating N-donor ligand 2,6-bis(1-(p-tolyl)-1H-1,2,3-triazol-4-yl)pyridine (BTTP) was investigated. The two isostructural lanthanide compounds [Ln(BTTP)3(OTf)3] (Ln = Eu (1), Sm (2); OTf = trifluoromethanesulfonate) were synthesized and fully characterized. The solid-state structures of both compounds were established by single-crystal X-ray diffraction. The complexation of Cm(III) and Eu(III) with BTTP in acetonitrile was studied using time-resolved laser fluorescence spectroscopy. With increasing BTTP concentration Cm(III) 1:2 and 1:3 complexes and Eu(III) 1:1 and 1:3 complexes are identified. The conditional stability constants of the 1:3 complex species with BTTP are log β3 = 14.0 for Cm(III) and log β3 = 10.3 for Eu(III). Both M(III) 1:3 complexes are prone to decomplexation with increasing acidity.
Gesehen am 29.06.2020